A Digital Patient Portal for Patients With Multiple Sclerosis - Voigt, Isabel; Benedict, Martin; Susky, Marcel; Scheplitz, Tim; Frankowitz, Sophie; Kern, Raimar; Müller, Olaf; Schlieter, Hannes; Ziemssen, Tjalf (Frontiers in Neurology, 2020)
Background: Multiple Sclerosis is a chronic inflammatory disease of the central nervous system that requires a complex, differential and lifelong treatment strategy, which involves high monitoring efforts and the accumulation of numerous medical data. A fast and broad availability of care- as well as patient-relevant data and a stronger integration of patients and participating care providers into the complex treatment process is desirable. The aim of the ERDF-funded project "Integrated Care Portal Multiple Sclerosis" (IBMS) was to develop a pathway-based care model and a corresponding patient portal for MS patients and health care professionals (HCPs) as a digital tool to deliver the care model. Methods: The patient portal was created according to a patient-centered design approach which involves both the patients and the professionals view. Buurmann's five iterative phases were integrated into a Design Science Research process. A problem analysis focusing on functions and user interfaces was conducted through surveys and workshops with MS patients and HCPs. Based on this, the patient portal was refined and a prototype of the portal was implemented using an agile software development strategy. Results: HCPs and patients already use digital hardware and are open for new technologies. Nevertheless, they desire improved (digital) communication and coordination between care providers. Both groups require a number of functions for the patient portal, which were implemented in the prototype. Usability tests with patients and HCPs are planned to consider whether it is deemed as usable, acceptable as well as functional and eventually it needs ameliorations. Discussion: After testing the patient portal for usability, acceptability and functionality, it will most likely be a useful and high-quality electronic health (eHealth) tool for patient management from day care to telerehabilitation. It implements clinical pathways in a manner which is comprehensible for patients. Future developments of the patient portal modules could include additional diseases, the integration of quality management and privacy management tools and the use of artificial intelligence to personalize treatment strategies.